2010
DOI: 10.1103/physrevb.81.205441
|View full text |Cite|
|
Sign up to set email alerts
|

Optimized Tersoff and Brenner empirical potential parameters for lattice dynamics and phonon thermal transport in carbon nanotubes and graphene

Abstract: We have examined the commonly used Tersoff and Brenner empirical interatomic potentials in the context of the phonon dispersions in graphene. We have found a parameter set for each empirical potential that provides improved fits to some structural data and to the in-plane phonon dispersion data for graphite. These optimized parameter sets yield values of the acoustic phonon velocities that are in better agreement with measured data. They also provide lattice thermal conductivity values in single-walled carbon … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
479
4
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 988 publications
(526 citation statements)
references
References 53 publications
31
479
4
1
Order By: Relevance
“…2nd generation REBO potential produces a more reliable function for simultaneously predicting bond lengths, energies, and force constants than the original version of the REBO potential [27]. On the other hand, optimized Tersoff and Brenner potential [23] parameters predict acoustic phonon (majority heat carriers in a material) velocity values to be in better agreement with the experimental data. In our work, we have done comparative computations using 2nd generation reactive empirical bond order potential (REBO) [27] and optimized Tersoff potential [23] because of their better accuracy in describing bond order characteristics and anharmonicity of both sp 2 and sp 3 carbon systems including different carbon structures like graphene, carbon nanotube and graphene nanoribbons.…”
Section: Interatomic MD Potentialssupporting
confidence: 70%
See 1 more Smart Citation
“…2nd generation REBO potential produces a more reliable function for simultaneously predicting bond lengths, energies, and force constants than the original version of the REBO potential [27]. On the other hand, optimized Tersoff and Brenner potential [23] parameters predict acoustic phonon (majority heat carriers in a material) velocity values to be in better agreement with the experimental data. In our work, we have done comparative computations using 2nd generation reactive empirical bond order potential (REBO) [27] and optimized Tersoff potential [23] because of their better accuracy in describing bond order characteristics and anharmonicity of both sp 2 and sp 3 carbon systems including different carbon structures like graphene, carbon nanotube and graphene nanoribbons.…”
Section: Interatomic MD Potentialssupporting
confidence: 70%
“…Interatomic potential, one of the most dictating fundamentals that influence the accuracy of thermal conductivity [11] can conveniently represent these interactions in a realizable form. Literature reported that the original Tersoff [21] potential tends to overestimate the thermal conductivity of graphene structures [22,23] while original REBO potential [24], adaptive intermolecular REBO or AIREBO [25] are found to underestimate the experimental data on the same [23,26]. 2nd generation REBO potential produces a more reliable function for simultaneously predicting bond lengths, energies, and force constants than the original version of the REBO potential [27].…”
Section: Interatomic MD Potentialsmentioning
confidence: 99%
“…The calculated DOS of pure sheet is consistent with the dispersion curve obtained from Boltzmann transport calculations using the same original potential [40,41]. Figure 5 presents the dispersion curve obtained from Boltzmann transport calculations and the DOS obtained from the EMD.…”
Section: Resultssupporting
confidence: 68%
“…The interatomic interactions for diamond and benzene are calculated using the adaptive intermolecular reactive empirical bond order (AIREBO) potential functions with the torsion term and van der Waals interaction included 47 . MD simulations based on AIREBO potential functions and parameters are validated to predict reasonably structural, mechanical and thermal properties of hydrocarbon system 48 . The time step for equation-ofmotion integration is set to 0.2 fs to assure energy conservation in the absence of thermostat coupling.…”
Section: Methodsmentioning
confidence: 99%